Finite element analysis of free vibration and buckling of thin-walled cylinders : effect of internal/external pressure and interference-fit - Yuan, Zhen (2014)
This final year project deals with the free vibration and buckling behaviors of thin cylinders. The analysis is carried out by finite element method. The commercial finite element software ANSYS is used for the purpose. Firstly, the convergence of natural frequencies with the mesh refinement is studied and then the natural frequencies of a single thin cylinder are determined under  No pressure  Increasing Internal pressure  Increasing External pressure The data are tabled then plotted and analyzed and compared, the corresponding mode shapes are also captured. Next, a compound cylinder with two cylinders joined by interference fit is considered. Again the natural frequencies and mode shapes of the compound cylinder are then determined under  No pressure and increasing interference but different frictional coefficient setting( Three scenarios: Ignore friction force, lubricated, clean and dry )  Fixed Interference with Increasing Internal pressure (clean and dry contact)  Fixed Interference with Increasing External pressure (clean and dry contact) The data are tabled then plotted and analysed and compared. Then the same models would be used for buckling analysis. First the buckling analysis of single cylinder would be performed, and then for the compound cylinders under........